Genomic diversity and adaptation of Salmonella enterica serovar Typhimurium from analysis of six genomes of different phage types - Pang, Stanley (BioMed Central, 2013)
BACKGROUND: Salmonella enterica serovar Typhimurium (or simply Typhimurium) is the most common serovar in both human infections and farm animals in Australia and many other countries. Typhimurium is a broad host range serovar but has also evolved into host-adapted variants (i.e. isolated from a particular host such as pigeons). Six Typhimurium strains of different phage types (defined by patterns of susceptibility to lysis by a set of bacteriophages) were analysed using Illumina high-throughput genome sequencing. RESULTS: Variations between strains were mainly due to single nucleotide polymorphisms (SNPs) with an average of 611 SNPs per strain, ranging from 391 SNPs to 922 SNPs. There were seven insertions/deletions (indels) involving whole or partial gene deletions, four inactivation events due to IS200 insertion and 15 pseudogenes due to early termination. Four of these inactivated or deleted genes may be virulence related. Nine prophage or prophage remnants were identified in the six strains. Gifsy-1, Gifsy-2 and the sopE2 and sspH2 phage remnants were present in all six genomes while Fels-1, Fels-2, ST64B, ST104 and CP4-57 were variably present. Four strains carried the 90-kb plasmid pSLT which contains several known virulence genes. However, two strains were found to lack the plasmid. In addition, one strain had a novel plasmid similar to Typhi strain CT18 plasmid pHCM2. CONCLUSION: The genome data suggest that variations between strains were mainly due to accumulation of SNPs, some of which resulted in gene inactivation. Unique genetic elements that were common between host-adapted phage types were not found. This study advanced our understanding on the evolution and adaptation of Typhimurium at genomic level.